1976
DOI: 10.1007/bf01317998
|View full text |Cite
|
Sign up to set email alerts
|

?Karshi? virus, a new flavivirus (Togaviridae) isolated fromOrnithodoros papillipes (Birula, 1895) ticks in Uzbek S.S.R.

Abstract: Three identical strains of an arbovirus were isolated from 475 Ornithodoros papillipes ticks collected in June, 1972, in burrows of the great gerbil (Rhombomys opimus Licht., 1882) in the environs of Beshkent, Karshinsk steppe, Uzbek S.S.R. The isolate was found to range among flaviviruses. Complement-fixation, agar diffusion precipitation and neutralization tests is tissue culture and mice indicated a one-way antigenic relationship between the isolate and West Nile virus. However, the pattern of differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Within the TBFV serocomplex, KSIV has the lowest overall MBE opening energies. Originally isolated from Ornithodoros papillipes ticks in Uzbekistan in 1972 76 it currently does not present history of infection in humans. Conversely, Powassan virus (POWV), another TBFV with negative MBE opening energy, first isolated in Powassan, Ontario, Canada in 1959 from a child who died of acute encephalitis 77 can cause transplacental infection 59 and has been associated with severe neuropathology and death in mice and human 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Within the TBFV serocomplex, KSIV has the lowest overall MBE opening energies. Originally isolated from Ornithodoros papillipes ticks in Uzbekistan in 1972 76 it currently does not present history of infection in humans. Conversely, Powassan virus (POWV), another TBFV with negative MBE opening energy, first isolated in Powassan, Ontario, Canada in 1959 from a child who died of acute encephalitis 77 can cause transplacental infection 59 and has been associated with severe neuropathology and death in mice and human 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis showed that GGYV was more related to the M-TBFV groups although it was discovered from seabird ticks (Major et al 2009 ). KSIV was first isolated from O. papillipes ticks collected in 1971 from Karshinsk steppe, Uzbekistan (Lvov et al 1976 ). Subsequently, it was isolated from H. asiaticum ticks collected in the north of Central Asia (Alma-Ata region of the Kazakh Soviet Socialist Republic) in 1976 (Khutoretskaya et al 1985 ).…”
Section: Families Unassigned To Any Ordermentioning
confidence: 99%
“…Within the TBFV serocomplex, KSIV has the lowest overall MBE opening energies. Originally isolated from Ornithodoros papillipes ticks in Uzbekistan in 1972 77 it currently does not present history of infection in humans. Conversely, Powassan virus (POWV), another TBFV with negative MBE opening energy, first isolated in Powassan, Ontario, Canada in 1959 from a child who died of acute encephalitis 78 can cause transplacental infection 59 and has been associated with severe neuropathology and death in mice and human 79 .…”
Section: Discussionmentioning
confidence: 99%